2022
DOI: 10.1002/er.7903
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of metal‐based gas diffusion layer containing rGO and graphite for proton exchange membrane fuel cells

Abstract: Proton exchange membrane fuel cell (PEMFC) offers various advantages such as high power density, high efficiency, low operating temperature, and very short start-up time, which make it a very good candidate to be used in electric vehicles propulsion systems. Among various cell components, the gas diffusion layer (GDL) plays an essential role in the energy conversion of the cell, hence the selection of GDL materials and the fabrication procedure are very important. In the present study, nickel mesh-based double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…The lack of guidelines for laboratory investigations on parameters such as current density and voltage impacts the accuracy of studies [126]. Recently, few more studies have been done on fuel cell technology in different fields of application to open the way for the researchers [127][128][129][130].…”
Section: Constraintsmentioning
confidence: 99%
“…The lack of guidelines for laboratory investigations on parameters such as current density and voltage impacts the accuracy of studies [126]. Recently, few more studies have been done on fuel cell technology in different fields of application to open the way for the researchers [127][128][129][130].…”
Section: Constraintsmentioning
confidence: 99%
“…Compared with the traditional two-fluid model, the liquid water saturation in PEMFCs with the baffle flow channel in their model was decreased significantly by taking the Forchheimer's inertial force shock into account. Moradizadeh et al [101] prepared a nickel mesh-based double layer GDL containing reduced graphene oxide (rGO) by printing the slurry onto the Ni mesh and found that the addition of rGO improved almost all the transport properties of GDL, but the electrical conductivity was not increased.…”
Section: Other Attempts To Improve Performance Of Gdlmentioning
confidence: 99%